Hardware Implementation of Diamond Search Algorithm for Motion Estimation - Rajabai C, Prayline; J, Harish; S, Sivanantham (International Journal of Engineering & Technology, 2018)
Motion estimation one of the advanced technique adapted in the industry for video coding and implemented in various applications. This work is focused on the efficient hardware implementation of the diamond search algorithm architecture. Among all the other Fast Search algorithms like three-step search, new three-step search, four-step search and diamond search (DS), the diamond search algorithm maintains the diamond shape search pattern and it gives faster search pattern and minimum absolute difference. When compared with the original diamond search (DS) algorithm, this modified diamond search algorithm requires less area and power maintaining the same performance. Other than the architectural level changes the low power synthesis is done and the results show that this design can be implemented effectively for an application that require fast search with low power requirements like IoT and sensor devices. The design has been implemented using Verilog HDL, synthesized using Synopsys DC compiler using 90nm technology.Â Â